Unidirectional Recombination of Antibiotic Resistance Genes Within Nasopharyngeal Pneumococcal Biofilm Consortia. (4th October 2017) - Lattar, Santiago; Brophy, Jennifer; Wu, Xueqing; Sakai, Fuminori; Vidal, Jorge
Abstract: Background: S. pneumoniae acquires genes for resistance to antibiotics, i.e., ampicillin, linezolid, streptomycin (Str), or trimethoprim (Trm), via transformation of DNA released by other pneumococci and closely related species while residing in the nasopharynx. Recombination by transformation occurs between naturally transformable strains when forming nasopharyngeal biofilms. We, therefore, investigated the direction of recombination of antibiotic resistance genes between transformable pneumococcal strains, including serotype 2 (S2) strain D39 and serotype 4 (S4) strain TIGR4. Methods: Chromosomal mutations, or insertion of genes into the chromosome, were made by traditional methods to generate strains resistant to Str, Trm, tetracycline (Tet), and erythromycin (Ery). Pairs of strains, each encoding an antibiotic-resistant determinant, were inoculated in a bioreactor simulating the human nasopharynx and recombinant bacteria harvested in plates containing two antibiotics. Identity of recombinants was investigated by a newly developed, high-throughput, serotyping assay and eDNA was quantified from supernatants using serotype-specific qPCR reactions. Results: Incubation of S2 Tet and S4 Str in the simulated nasopharynx led to the generation of Spn Tet/Str recombinants peaking after 8 hours at a recombination frequency (rF) of 1.7 × 10 −3 . Recombination by transformation was confirmed by treatment with DNaseI (rF < 6.7 × 10 −7 ). A high-throughput method of pneumococcal serotyping demonstrated that double-resistant bacteria were S2 Tet/Str and, therefore, that unidirectional recombination had occurred. While DNA from both strains was released into the supernatant, eDNA from the donor strain (S4) was ~6, 000-fold increased at 8 hours postinoculation. Unidirectional recombination was observed whether the donor, or recipient, encoded resistance to Trm, Str, Tet, or Ery. Recombination experiments with a recipient lacking production of CSP1, or the type IV pili, (S2Δ comC Str, or S2Δ comGA Str, respectively), confirmed that eDNA is taking up by transformation. Conclusion: Recombination of antibiotic-resistant determinants between transformable pneumococcal strains, in the nasopharynx, was unidirectional. It has important implications for interventions aimed to stop the spread of antibiotic-resistant strains. Disclosures: All authors: No reported disclosures.